Monsters: a companion - Bacon, Simon (Genre fiction and film companions, 2020)
CONTENTS: Home – Angela M. Smith: Madness: The Babadook (Kent, 2014) – Monsters of Mental Illness – Simon Bacon: Domestic Abuse: The Invisible Man (Whannell, 2020) – Domestic Monsters – Phil Fitzsimmons: Paedophilia: The Nightingale (Kent, 2018) – Monsters of Abuse –Agnieszka Kotwasinìska: Immigrants: The Lure (Smoczyñska, 2015) – Monstrous Outsiders – Society – John Edgar Browning: The Mask: Slasher Cinema (1978–1998) – Teaching the Monster – Lauren Rosewarne: The Cyberbully: Cyberbully (Binamé, 2011) – Monsters of Cyberspace – Anthony Curtis Adler: Lady Gaga: Stefani Joanne Angelina Germanotta (1986–present) – Monsters of Celebrity – Alexandra Heller-Nicholas: The Slit-Mouthed Woman: Carved (Shiraishi, 2007) – Monsters of Urban Legend – W. Scott Poole: Melmoth: Melmoth (Perry, 2018) – Monsters of War – Cultural Intersections – Benjamin Baumann: Phi Krasue: Inhuman Kiss (Mongkolsiri, 2019) – Thai Monsters – Inés Ordiz: La habitación del desahogo (2012) – Mexican Monsters – Gail de Vos: Baba Yaga: Hellboy (Mignola, 1997–2004) – Russian Monsters – Partha Mitter: Deumo: Indiana Jones and the Temple of Doom (Spielberg, 1984) – Monsters of Colonialism – Yasmine Musharbash: The Hairies: Cleverman (Griffen, 2016–2017) – Aboriginal Monsters – Gender – Eddie Falvey: Satan: The Witch (Eggers, 2015) – Patriarchal Monsters – Emily Brick: Warlocks: AHS Apocalypse (Murphy and Falchuk, 2011–present) – Monsters of Masculinity – Craig Ian Mann: She-Wolves: When Animals Dream (Arnby, 2014) – Monsters of Femininity – Daniel Sheppard: Serial Killers: Bates Motel (Ehrin, 2013–2017) – The Queer Monster – Murray Leeder: The Skeleton: Game of Thrones (Benioff, 2011–2019) – Monsters of Death – Partha Mitter: Deumo: Indiana Jones and the Temple of Doom (Spielberg, 1984) – Monsters of Colonialism –Yasmine Musharbash: The Hairies: Cleverman (Griffen, 2016–2017) – Aboriginal Monsters – Gender – Eddie Falvey: Satan: The Witch (Eggers, 2015) – Patriarchal Monsters – Emily Brick: Warlocks: AHS Apocalypse (Murphy and Falchuk, 2011–present) – Monsters of Masculinity – Craig Ian Mann: She-Wolves: When Animals Dream (Arnby, 2014) – Monsters of Femininity – Daniel Sheppard: Serial Killers: Bates Motel (Ehrin, 2013–2017) – The Queer Monster – Murray Leeder: The Skeleton: Game of Thrones (Benioff, 2011–2019) – Monsters of Death – Futures – Leah Richards: Clones: Orphan Black (Manson and Fawcett, 2013–2017) – Monsters of Reproduction – Dahlia Schweitzer: The Master: The Strain (del Toro and Hogan, 2014–2017) – Monsters of Contagion – Carl H. Sederholm: The Ecomonster: Megalohydrothalassophobia (Abhorrence, 2018) – Monsters of the Anthropocene –Gerry Canavan: Aliens: District 9 (Blomkamp, 2009) – Monsters of Hybridity – Elana Gomel: Zombie: The Girl with All the Gifts (Carey, 2014) – Posthuman Monsters – Patricia MacCormack: Afterword: Becoming Monstrous and the Monster Becoming: Hannibal (Fuller: 2013–2015) – Index.
Keywords: Aufsatzsammlung; Fernsehserie; Film; Literatur; Ungeheuer